2011
DOI: 10.3109/00952990.2011.568081
|View full text |Cite
|
Sign up to set email alerts
|

Tipranavir/Ritonavir Induction of Buprenorphine Glucuronide Metabolism in HIV-Negative Subjects Chronically Receiving Buprenorphine/Naloxone

Abstract: This study further elucidates the effects of TPV/r on glucuronidation. The current evaluation of glucuronide metabolites of BUP and norBUP are suggestive of combined inhibition of Uridine diphosphate (UDP)-glucuronosyltransferase of the 1A family and cytochrome P450 3A4 that spares UGT2B7 leading to a shunting of BUP away from production of norBUP and toward BUP-3G as seen by a statistically significant increase in the AUC of BUP-3G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Tipranavir significantly altered the disposition of norbuprenorphine without producing a pharmacodynamic effect [184]. This reduction in norbuprenorphine concentrations is suggestive of a combined inhibition of the UGT 1A family and CYP 3A4 that spares UGT 2B7 leading to a shunting of buprenorphine away from the production of norbuprenorphine and towards buprenorphine-3-glucuronide [185]. …”
Section: Interactions Between Buprenorphine and Specific Antiretrovirmentioning
confidence: 99%
See 1 more Smart Citation
“…Tipranavir significantly altered the disposition of norbuprenorphine without producing a pharmacodynamic effect [184]. This reduction in norbuprenorphine concentrations is suggestive of a combined inhibition of the UGT 1A family and CYP 3A4 that spares UGT 2B7 leading to a shunting of buprenorphine away from the production of norbuprenorphine and towards buprenorphine-3-glucuronide [185]. …”
Section: Interactions Between Buprenorphine and Specific Antiretrovirmentioning
confidence: 99%
“…The increase in buprenorphine and the reduction in norbuprenorphine are reminiscent of the tipranavir/ritonavir inhibition of 3A4 and the shunting of buprenorphine metabolism away from norbuprenorphine. [185]. Based on this data, boceprevir can be safely dosed in patients on methadone or buprenorphine.…”
Section: Interactions Between Hepatitis C Antivirals and Methadone Ormentioning
confidence: 99%
“…The lack of an interaction between fenofibrate and lopinavir‐ritonavir and between fenofibrate and ritonavir is likely explained by fenofibric acid being largely glucuronidated by UGT2B7, which does not appear to undergo induction by ritonavir, despite ritonavir's ability to modulate the activity of other UGT enzymes such as UGT1A1 and UGT1A4 . Additionally, in contrast to the reduction in gemfibrozil absorption that was previously observed with concurrent administration of lopinavir‐ritonavir, neither lopinavir‐ritonavir nor ritonavir alone significantly affected fenofibric acid absorption in the current investigation.…”
Section: Discussionmentioning
confidence: 85%
“…Lopinavir‐ritonavir and ritonavir alone were chosen for coadministration with fenofibrate in this study based on the previously described interaction between lopinavir‐ritonavir and gemfibrozil (a fibric acid derivative that is chemically similar to fenofibrate) and because fenofibric acid is largely biotransformed through glucuronidation and several glucuronidation pathways are known to undergo induction in the presence of ritonavir and/or lopinavir‐ritonavir . In addition, although lopinavir‐ritonavir is no longer considered a recommended protease inhibitor for inclusion in cART regimens, it continues to be a widely used protease inhibitor throughout the world and therefore remains clinically relevant .…”
Section: Discussionmentioning
confidence: 99%
“…As such, studies have shown a statistically significant increase in buprenorphine plasma levels in subjects concomitantly administered buprenorphine and ART regimens involving ritonavir. [249][250][251][252] This type of DDI increases the risk of buprenorphine toxicity and can create the potential for opioid excess. Despite this risk, subjects in these studies did not show any signs of opioid excess or withdrawal 198,212,[249][250][251][252][253] (Table S6).…”
Section: Buprenorphinementioning
confidence: 99%